2015
DOI: 10.3109/08037051.2014.997082
|View full text |Cite
|
Sign up to set email alerts
|

How do we measure blood pressure at home?

Abstract: Awareness of both patients and physicians about the validation status of HS is not enough. Some complaints from patients may be associated with using non-validated HS. There is a need for a policy or standard criteria for HS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, the limited availability of calibrated and validated machines limits the use of self-measurement of BP at home. 14,15…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the limited availability of calibrated and validated machines limits the use of self-measurement of BP at home. 14,15…”
Section: Discussionmentioning
confidence: 99%
“…However, the limited availability of calibrated and validated machines limits the use of self-measurement of BP at home. 14,15 Although there are a number of studies evaluating the importance and suitability of DAU for assessing BP, there is limited evidence regarding the optimum time for monitoring of the BP. 6,7,9,16 A satisfaction survey by Dunlop et al found that waiting in DAU for long periods (test results and review by medical officer) was viewed negatively by the women.…”
Section: Discussionmentioning
confidence: 99%